2023
DOI: 10.1111/jfpe.14286
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted hot air drying characteristics of Phyllanthus emblica

Abstract: The ultrasound-assisted hot air drying characteristics of Phyllanthus emblica was investigated in this paper. The effects of hot air temperature (60 C, 65 C, 70 C, and 75 C), ultrasonic pretreatment time (2, 4, 6, and 8 min), and ultrasonic power (200, 250, 300, and 350 W) on the drying rate, energy consumption, color change, and rehydration rate were evaluated and compared. It was found that the drying rate of Phyllanthus emblica increased with the hot air temperature. The drying time of Phyllanthus emblica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Reabsorption is a complex process in regenerating dried food that involves contact with water (Lin et al, 2022). Therefore, rehydration ratio can be considered a criterion for measuring the damage of the drying process to food (Huang et al, 2023). The rehydration ratio depends on cell structure disruption, chemical changes, processing conditions, sample preparation and sample composition during drying.…”
Section: Introductionmentioning
confidence: 99%
“…Reabsorption is a complex process in regenerating dried food that involves contact with water (Lin et al, 2022). Therefore, rehydration ratio can be considered a criterion for measuring the damage of the drying process to food (Huang et al, 2023). The rehydration ratio depends on cell structure disruption, chemical changes, processing conditions, sample preparation and sample composition during drying.…”
Section: Introductionmentioning
confidence: 99%
“…Energy consumption is a significant factor to consider when weighing the advantages and disadvantages of drying because drying is an energy-consuming process. For the industry to use less energy, energy consumption during drying needs to be substantially reduced [ 43 ]. The study findings demonstrated that humidification treatment minimized drying time and energy use ( Figure 8 ).…”
Section: Experimental Research and Analysismentioning
confidence: 99%